Pengaruh Ukuran Perusahaan Terhadap Audit Delay Pada Perusahaan Sektor Consumer Non-Cyclicals Tahun 2020-2022 - Margareth Srinauli; Grace Priscilla; Linda Kartika; Trinandari Prasetya Nugrahanti (Jurnal Akuntan Publik, 2024)
One of the causes of delays in the publication of financial reports is the process of completing audits by accountants which takes quite a long time, which is called audit delay. Company size is one of several elements that can influence audit delay. The purpose of this study is to investigate how firm size affects audit delay. Using secondary data from the websites www.idx.co.id and the official websites of the companies, the research method used is descriptive statistical analysis, classical assumption test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple regression analysis, determination coefficient test, significant F model test, and the significance test of independent variables (T-test). Purposive sampling was utilized to determine the sample size, which came out to be 207 in the non-cyclical consumer business sector company listed on the Indonesia Stock Exchange for the 2020–2022 period. The study's findings show that the audit delay is significantly impacted negatively by the company's size. The implication is that there is a significant influence of company size on audit delay.